Implementasi Teori Humanistik Pada Peserta Didik Kelas IV Di MIN 4 Jember: Implementation Of Humanistic Theory In Fourth Grade Students In MIN 4 Jember - Zein, Ahmad Muzakki; Ramadhan, Firman Aulia; Farihah, Umi (IJIT: Indonesian Journal of Islamic Teaching, 2022)
Humanistic learning is a humanist-based learning model. Students are seen as whole and unique individuals in humanistic learning. Students have different levels of potential and intelligence. Humanistic education seeks to humanize man by recognizing and developing his potential. Therefore, researchers are interested in researching the use of humanistic learning in MIN 4 Jember. Humanistic education can be used in the implementation of learning in school. This study takes a qualitative approach. Researchers gather information through interviews, observation, and documentation. Pre-Field, fieldwork, and data analysis are the stages of research. The study's findings concluded that (1) (a) the concept of humanistic learning in MIN 4 Jember is to humanize learning that values, explores, serves, and helps learners develop various types of potential. (2) the implementation of humanistic learning in MIN 4 Jember includes (a) fun and exciting learning for students. (b) print and electronic media, books, and the environment are used as media, tools, and learning resources. (c) no unilateral sanctions are imposed on students; and (d) teachers act as educators, mentors, motivators, and facilitators. (e) the role of students in teaching and learning activities is to be actively involved and feel comfortable during the learning process. (f) helpful factors include competent, committed teachers and adequate facilities. (g) inhibiting factors include the existence of teachers who are less creative and have limited expertise. Pembelajaran pendidikan humanistik adalah model pembelajaran yang berbasis humanis. Siswa dipandang sebagai individu yang utuh dan unik dalam pembelajaran humanistik. Siswa memiliki tingkat potensi dan kecerdasan yang berbeda-beda. Pendidikan humanistik berusaha memanusiakan manusia dengan mengenali dan mengembangkan potensi yang dimilikinya. Oleh karena itu, peneliti tertarik untuk meneliti penggunaan pembelajaran humanistik di MIN 4 Jember. Pendidikan humanistik dapat digunakan dalam pelaksanaan pembelajaran di sekolah tersebut. Penelitian ini mengambil pendekatan kualitatif. Peneliti mengumpulkan informasi melalui wawancara, observasi, dan dokumentasi. Pra-lapangan, pekerjaan lapangan, dan analisis data merupakan tahapan-tahapan penelitian. Temuan penelitian menyimpulkan bahwa (1) (a) konsep pembelajaran humanistik di MIN 4 Jember adalah memanusiakan pembelajaran yang menghargai, menggali, melayani, dan membantu peserta didik dalam mengembangkan berbagai jenis potensi. (2) Implementasi pembelajaran humanistik di MIN 4 Jember meliputi (a) pembelajaran yang menyenangkan dan menarik bagi siswa. (b) media cetak dan elektronik, buku, dan lingkungan digunakan sebagai media, alat, dan sumber belajar. (c) tidak ada sanksi sepihak yang dikenakan kepada siswa; dan (d) guru berperan sebagai pendidik, pembimbing, motivator, dan fasilitator. (e) peran siswa dalam kegiatan belajar mengajar adalah terlibat aktif dan merasa nyaman selama proses pembelajaran. (f) faktor yang membantu meliputi guru yang kompeten, berkomitmen dan fasilitas yang memadai. (g) faktor penghambat meliputi masih adanya guru yang kurang kreatif dan memiliki keahlian yang terbatas.